Killer Bees - Rollason, Jane (Cambridge University Press United Kingdom, 2009)
A decision to borrow her mum's car with a friend leaves Jo worrying about the consequences. When she eventually returns home, she finds no one there. A new breed of dangerous bees has escaped from a research center and everyone has fled their homes in search of safety. Jo must rejoin her missing family.
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents.
Keywords: Reading books; Elementary/lower-intermediate level; Language Learning; Fiction; Horror